Analysis of clinical and microbiological characteristics of invasive Klebsiella pneumoniae liver abscess syndrome - Li Gu; Yue Wang; Han Wang; Dong Xu (BMC Infectious Diseases)
Abstract Background Invasive Klebsiella pneumoniae liver abscess syndrome (IKPLAS) is emerging as a new disease worldwide, threatening human health. This study aimed to investigate the clinical and microbiological features of IKPLAS in order to detect this syndrome early and select antibiotics appropriately. Methods Medical data from patients in Tongji Hospital, China, diagnosed with Klebsiella pneumoniae liver abscess (KPLA) between 2015 and 2023 was collected and analyzed retrospectively. Results The study included 208 patients with KPLA, 41 with IKPLAS, and 167 with non-IKPLAS (NIKPLAS). Multivariate logistic regression analysis demonstrated that symptoms in other organ systems (including ocular, pulmonary, and neurological symptoms) (p = 0.001) and a sequential organ failure assessment (SOFA) score ≥ 4 within 48 h of admission (P = 0.002) were significant risk factors for IKPLAS. Patients with IKPLAS had a higher risk of developing multiple organ dysfunction (MODS), and a PCT ≥ 10 ng/mL was identified as an independent risk factor for MODS (p = 0.01). IKPLAS was associated with significantly prolonged hospital stays and unfavorable outcomes (all p < 0.05). There were no significant differences in microbiological characteristics between IKPLAS and NIKPLAS, including the antimicrobial susceptibility pattern and resistance profile of Klebsiella pneumoniae (KP) (all p > 0.05). In this study, KP isolates were susceptible to most antibiotics, with low rates of drug resistance. Specifically, a total of five carbapenem-resistant strains (2.6%) and seven multidrug-resistant strains (3.6%) were detected, all of which were derived from the NIKPLAS group. Conclusions Symptoms in other organ systems and the SOFA score ≥ 4 within 48 h of admission were significant predictors for IKPLAS. This study elucidated the antimicrobial susceptibility profile of liver abscess-associated KP strains, providing a reference for the early initiation of rational and effective antimicrobial therapy in patients with KPLA.